Evaluation of tribological characteristics of technical oils with fullerene compositions - Kravtsov, A.G. (Problems of Tribology, 2020)
The paper presents experimental studies of the tribological characteristics of liquid lubricants of various viscosity classes and various groups of operation when using fullerene compositions. Tribological characteristics were evaluated on a four-ball friction machine according to GOST 9490. The use of fullerene compositions in the form of a finely dispersed fullerene powder, pre-dispersed (dissolved) in vegetable high oleic oils, for example, rapeseed, with the subsequent addition of the resulting composition to technical oils of various viscosity classes and various groups of operation, leads to the following positive effect. The anti-wear properties of oils, which are assessed by the wear indicator, increase by 20,0…30,7 %, and the critical load on 18,8…25,0%. These indicators significantly exceed similar indicators when using fullerene fine powders without preliminary dispersion in vegetable oils, where the effect is on the border 11,1…15 %. Fullerene additives do not affect the extreme pressure properties of base oils, which are assessed by the scuffing load. This result makes it possible to state that the way to improve the tribological properties of lubricants by introducing a fine powder of fullerenes into base technical oils is ineffective. The experimental results obtained confirm the hypothesis about the possibility of the micelle formation mechanism in the lubricant under the action of the electrostatic field of the friction surface. The presence of a surfactant solvent (vegetable oil) allows you to "start" the micelle formation process at lower fullerene concentrations and to obtain the effect of increasing anti-wear properties.